Is Gender Destiny? Gender Bias and Intergenerational Educational Mobility in India - M. Shahe Emran; Hanchen Jiang; Forhad Shilpi (Global Labor Organization (GLO), 2021)
We develop a model of intergenerational educational mobility incorporating gender bias against girls in the family, school, and labor market. Mobility and investment equations from the model are estimated for India using data not truncated by coresidency. The standard linear model misses important heterogeneity and yields misleading conclusions. Daughters of uneducated fathers face lower relative and absolute mobility (rural and urban). We find gender equality in absolute mobility for children of urban college educated fathers, but not in rural areas. Theoretical insights help understand the mechanisms. Parental nonfinancial inputs, unwanted girls, and patrilineal states are important for explaining the findings.
Keywords: I24; J62; J16; O20; 330; Gender Bias; Intergenerational Mobility; Education; Becker-Tomes Model; Heterogeneity; Son Preference; Unwanted Girls; India; Patrilineal; Matrilineal; Coresidency Bias